Molecular characterization of PI*Shangzhou, a SERPINA1 allele from continental China encoding a defective alpha-1-antitrypsin - Hernández-Pérez, José M.; González Carracedo, Mario A.; García, Angelines Concepción; Pérez, José A. Pérez (Frontiers in Pediatrics, 2022)
Alpha-1-antitrypsin deficiency (AATD) is a heritable condition that predisposes to respiratory and hepatic complications. Screenings in East Asia human populations for the AATD alleles most commonly found among Caucasians have yielded poor outcomes. Serum alpha-1-antitrypsin (AAT) levels, AAT phenotypes, and sequences of SERPINA1 gene were examined in a Chinese child with a moderate deficit of serum AAT, who had suffered several episodes of liver disease, as well as in his first-order relatives. Results allowed the identification of PI*Shangzhou, a novel SERPINA1 defective allele, which has been characterized by a L276R substitution, found in a SERPINA1-M3 genetic background. Moreover, potential effects of PI*Shangzhou mutation over the AAT structure were studied by 3D homology modelling. The presence of an arginine residue at position 276 could destabilize the tertiary structure of AAT, since it occurs at a highly conserved hydrophobic cavity in the protein surface, and very close to two positively-charged lysine residues. Attending to the frequency of R276 variant reported in databases for individuals of East Asian ancestry, the PI*Shangzhou allele may explain the global prevalence of the PiS phenotype observed in China.